Thursday

April 24, 2014

April 24, 2014

Posted by **Amy** on Friday, October 28, 2011 at 2:11am.

y=-3/4x + 1/4

y=3/4x - 3/4

- Math -
**Jai**, Friday, October 28, 2011 at 3:21amadd the two equations to get y alone:

y = -3/4x + 1/4

y = 3/4x - 3/4

--------------------------

2y = -2/4

y = -1/4

then substitute this value of y to either of the equations and solve for x. in this case let's substitute this to the first give equation:

y = -3/4x + 1/4

-1/4 = -3/4x + 1/4

-1/4 - 1/4 = -3/4x

(-2/4 = -3/4x)*4

-2 = -3x

x = 2/3

hope this helps~ :)

**Related Questions**

math, algebra - How do I solve for the following: Directions solve each literal ...

Math - Okay .. Im working on Linear Equations and am VERY confused can someone ...

bobpursly,.math - Ok, assume it equals zero. 2x + 3y -6=0 subtract 3y from each ...

Discrete Math - True or False? Homogeneous linear recurrence equations are ...

Linear - 3x/4 + 6= -12 I know this is a linear equation but how solve it and ...

algebra - solve each literal equation for the indicated variable linear equation...

MATH - I NEED TO SOLVE FOR Y AND X im getting rele confused on this. ok here is ...

Algebra 1 - What is an equation of a line perpendicular to the line with ...

maths - use the substitution method to solve the linear system. 1. 3x=9 -x+2y=9 ...

math - how do you solve this linear equation? x/3-1/3=-5 I do not understand ...